Interferon-α and -β restrict polyomavirus JC replication in primary human fetal glial cells: Implications for progressive multifocal leukoencephalopathy therapy - Go, Juliene Kimberly G. (Animo Repository, 2007)
One of the major limitations of highly active antiretroviral therapy is its inability to inhibit the replication of polyomavirus JC (JCV), the etiologic agent of progressive multifocal leukoencephalopathy (PML), an acquired immunodeficiency syndrome-defining illness. We previously demonstrated the induction of interferon (IFN)-stimulated genes (ISGs) by JCV. In the present study, we characterize the specific viral events required to induce ISGs and the potential antiviral effects of type I IFN on JCV replication in human fetal glial cells in the presence and absence of type I IFNs. Productive JCV replication was essential for the induction of the antiviral host response. JCV replication at all steps was significantly inhibited in the presence of IFN, and neutralizing anti-IFN antibody rescued the inhibitory effect of IFN. These results support the use of IFN as an adjunct therapy for patients with PML. Because IFN cannot cross the blood-brain barrier to achieve its direct antiviral effect, intrathecal administration of IFN is warranted.